Dinamika Relasi Nabi SAW dengan Yahudi Perspektif Teori Konflik Ralf Dahrendorf - A'yun, Qurrota; Zulfikri, Zulfikri; Hakim, Luqmanul (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2022)
This article aims to find out the form of connection that occurred between the Prophet Muhammad and the Jews in Madina. The population of Madina consists of a wide variety of tribes, religions, and social and economic levels. In this situation, it is perilous for conflict to occur. It is known that there were three popular Jewish groups in Madina, namely the Banu Qainuqā, the Banu Naḍīr, and the Banu Qurayẓah. In addition, the author wants to explore the factors that influence the dynamics of the connection between the Prophet Muhammad SAW and the Jews. In order to find out the answer to the question, this research was conducted using qualitative methods from the perspective of Ralf Dahrendorf's conflict theory. The results of this study were: First, the relations started when the Prophet Muhammad SAW moved to Madina and the involvement of the Jews in a mutual agreement. Furthermore, the axis of the conflict began to appear when there was a debate on the issue of faith and worship. Second, the factors that influenced the relations of the Prophet Muhammad SAW in the perspective of conflict theory were three factor; the factor of the seizure of authority, the ethnocentrism factor and transferred culture factor.